Analisis potensi energi panas matahari untuk digunakan pada sistem refrigerasi absorpsi di bangunan perkantoran - Yusvardi Yusuf; Imron Rosyadi; Mekro Permana Pinem (Badan Kerja Sama Teknik Mesin Indonesia, 2022)
Conventional cooling systems used in office buildings are one of the causes of ozone layer depletion and greenhouse effects. It requires the advancement of new technologies that are safe for the environment to be used in cooling systems in office buildings. Absorption cooling systems using solar thermal energy have many advantages by using non-destructive working fluids such as water, or in the form of saline solutions. This is a form of energy saving and safe for the environment. In order to obtain real and objective measurement data, testing is performed in two stages, namely the test equipment testing stage and the second stage is data collection when the test equipment is fully operational. The test equipment can be used in stand-alone systems or conventional air conditioners. In the test, it is known that the average percentage of solar thermal energy consumption per day is 40% of total energy so due to solar thermal energy consumption, the average COP value of this system per day is 2 and this value is greater than similar absorption cooling systems. conventional, then by knowing the value of solar energy consumption, can be seen the value of CO2 emissions reduction of 143.8 kg CO2 per day.